Comprehensive study of effects of filler length on mechanical, electrical, and thermal properties of multi-walled carbon nanotube/polyamide 6 composites. (October 2019) - Jang, Han Gyeol; Yang, Beomjoo; Khil, Myung-Seob; Kim, Seong Yun; Kim, Jaewoo
Abstract: In spite of active studies on multi-walled carbon nanotube (MWCNT)-incorporated polymer, MWCNTs of different thickness and lengths have been employed. Here, the effects of MWCNT morphology, specifically its length, on the mechanical, thermal, and electrical properties of MWCNT/polymer composites were examined in comparison with theoretical modeling. Field-emission scanning electron microscopy and micro-computed tomography observations revealed that short MWCNTs were dispersed more uniformly than long MWCNTs in a polyamide 6 (PA6) polymer. Correlation of this result with the tensile performance revealed that at low MWCNT concentrations the long-MWCNT/PA6 composite showed superior tensile properties since the effect of length was dominant. However, at high MWCNT concentrations, the short-MWCNT/PA6 showed superior tensile properties to the long-MWCNT/PA6 due to the better dispersion of the former. The thermal conductivity gradually improved with increasing MWCNT concentration, showing larger improvement for the long-MWCNT/PA6, while the electrical conductivity reached percolation threshold at 1 wt% for both MWCNTs.